2011
DOI: 10.1007/s11046-011-9461-3
|View full text |Cite
|
Sign up to set email alerts
|

Single Oral Paracoccidioidomycosis Mimicking Other Lesions: Report of Eight Cases

Abstract: Paracoccidioidomycosis is a fungal infection caused by Paracoccidioides brasiliensis. It is an endemic disease, representing a serious health problem in Latin American countries. This infection primarily affects the lungs and is acquired by inhalation of the fungus. It can spread to other organs and tissues, mainly the oral cavity affecting more adult men from 30 to 50 years of age. On clinical presentation, several signs associated with impaired general and nutritional conditions can be noted. Oral manifestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 24 publications
3
20
1
11
Order By: Relevance
“…This specific evaluation addresses morphological characteristics of the pathogen as to spore size, type of gemulation, and presence of septate hyphae. [11]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This specific evaluation addresses morphological characteristics of the pathogen as to spore size, type of gemulation, and presence of septate hyphae. [11]…”
Section: Discussionmentioning
confidence: 99%
“…Since PCM is a systemic disease, the treatment is conducted by the physician and the regression of oral lesion must be followed by dentist. [11] Multidisciplinary management allows the adoption of the best supporting measures to address the systemic changes associated to disease, like malnutrition and other comorbidities, as well as dental treatment. In addition, it should be emphasized that follow-up for extended periods is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic ulcers are usually painful and do not heal spontaneously; these ulcers characteristically have a red granulomatous or berry-like surface. In our cohort, 13.79% patients had macrochelia, which some authors report as a frequently observed manifestation in adult chronic multifocal PCM [5,6,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 67%
“…These ulcerations can be multifocal or single (Godoy & Reichart). However, when the oral manifestation is single, others lesions, particularly squamous cell carcinoma, must be included in the differential diagnosis (de Oliveira Gondak et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Other denominations were Brazilian Blastomycosis, and South American Blastomycosis. It is an endemic disease representing a serious health problem for Latin American countries, especially Ecuador, Colombia, Venezuela, Argentina and Brazil (Godoy & Reichart, 2003;de Oliveira Gondak et al, 2012). This last country contributes with the highest incidence of the disease in the world, occupying the eighth place among causes of death from infectious, recurrent, chronic and parasite diseases (Coutinho et al, 2002).…”
Section: Paracoccidioidomycosis (Pcm) Is a Fungal Infection Caused Bymentioning
confidence: 99%